The analgesic promise of seaweeds: a systematic review of preclinical and clinical evidence - Belda-Antolí, Mariola; Fenández-Ehrling, Nadia; Jaenada-Carrilero, Eloy; Baraja-Vegas, Luís; Ferrer-Torregrosa, Javier; Falaguera-Vera, Francisco J.; Vicente-Mampel, Juan (Frontiers in Marine Science, 2025)
BackgroundSeaweeds are typically considered a part of traditional diets in several Asian countries and have recently acquired significant attention owing to the therapeutic potential of their bioactive compounds. sulfated polysaccharides, polyphenols, and proteins are the most common seaweed-derived substances with pronounced antioxidant and anti-inflammatory properties. However, the analgesic effects of these compounds have not yet been well established.MethodsAn extensive systematic search of four databases, including PubMed, Scopus, Web of Science, and the Cochrane Library, was conducted until May 2025. Preclinical and clinical studies evaluating the analgesic effects of seaweed-derived compounds were included in this review.ResultsPreclinical studies have shown significant antinociceptive effects of various seaweed-derived substances. Sulfated polysaccharides demonstrated a dose-dependent peripheral analgesic effect, whereas central analgesic effects appeared at the highest doses. Phlorotannin-rich polyphenols also showed substantial peripheral analgesic effects, reaching 90.16% inhibition in the writhing test, and prominent central analgesic responses lasting 120 min. Furthermore, lecithin extracts exhibited significant peripheral antinociceptive effects with favorable safety profiles. Evidence from human studies is limited to four small trials (total n = 91). In one study (n = 30) on mild knee osteoarthritis, a multi-mineral seaweed formulation (Aquamin+) produced greater pain reduction than glucosamine. Risk of bias assessment showed an overall low-to-moderate quality across the included studies.ConclusionSeaweed extracts exhibit promising peripheral and central antinociceptive effects. However clinical data remain preliminary and heterogenous. Further research is warranted to standardize the extracts, explore chronic pain applications, and validate the findings in large-scale human trials.Clinical trial registrationhttps://www.crd.york.ac.uk/prospero/, identifier systematic review is registered with PROSPERO CRD420251078862.